Effects of electroacupuncture on stress and anxiety-related responses in rats - BASSETTO,RICARDO M. (2017)
ABSTRACT The aim of this work was to investigate if eletroacupuncture at PC6 would modulate the stress-induced anxiety-like behavior and the level of activation of several brain areas. Rats were distributed in groups: control; submitted to immobilization; submitted to immobilization and eletroacupuncture at PC6 or at the tail. Immobilization increased grooming and decreased stretched attend postures and the time spent in the open arms of the ele-vated plus-maze. Eletroacupuncture at PC6 or tail canceled the effect of immobilization on grooming and attenuated the stretched attend posture. Immobilization increased Fos-immunoreactivity in the prefrontal cortex, medial and central amygdala, paraventricular and dorsomedial nuclei of the hypothalamus, lateral hypothalamus, dentate gyrus, CA1, CA2 and CA3 hippocampal areas. The activation of paraventricular, dorsomedial nuclei and prefrontal cortex by immobilization was canceled by electroacupuncture at PC6 and attenuated by electroacupuncture in the tail. The activation of the other areas was canceled by electroacupuncture in PC6 or the tail. It is concluded that immobilization induced anxiety-like behavior that was moderately attenuated by eletroacupuncture with difference between the stimulation in PC6 or the rat tail. Eletroacupuncture showed specificity concerning to the attenuation of the effects of immobilization in the CNS areas related to the stress response, anxiety and cardiovascular system.